Adventure Education and the Acculturation of First-Generation Chinese Canadians in Vancouver, Canada. (June 2014) - Lo, Simon; Gidlow, Bob; Cushman, Grant
This article reports on research that demonstrates how parents in first-generation Chinese families in Vancouver, Canada, most of them from Hong Kong, control their children's involvement in local adventure education (AE) programs and in so doing minimize the likelihood of intergenerational culture conflict involving those children. The research is based on 28 face-to-face, digitally recorded interviews with 14- to 18-year-old participants, their parents, and instructors, in two AE programs in Vancouver, Canada. The interviews were conducted in 2009.